Body composition and sexual hormones for the glucose control of autoimmune diabetes in males: are they necessary to predict diabetes-related complications? - García Ramírez, Mireia; Rebollo Román, Ángel; Palomares Ortega, Rafael; Alonso-Echague, Rosario; Calle-Castro, María Luisa; Gálvez Moreno, María Ángeles; Molina Puerta, María José; Herrera-Martínez, Aura D. (Frontiers in Endocrinology, 2023)
Background Glucose control in diabetes is essential for avoiding diabetes-related complications. Aim To determine the impact of body composition and sexual hormones in glucose control and diabetes-related complications, in males with autoimmune diabetes. Patients and methods Thirty-nine patients with autoimmune diabetes and flash glucose monitoring were included. A morphofunctional nutritional evaluation with bioelectrical impedance vector analysis (BIVA), abdominal adipose tissue ultrasound, rectus femoris ultrasound and biochemical parameters, was performed Results Strong, positive correlations were observed between body composition parameters, biochemical variables and sexual hormones (p<0.05). Adipose tissue measured by BIVA and ultrasound was more significantly associated with glucose control (including time in range >70%, glucose variability <36% determined by flash glucose monitoring; p<0.05) and the presence of microvascular/macrovascular complications (p<0.05) than lean mass. After adjusting by the duration of diabetes, BMI, abdominal circumference, fat mass and phase angle increased the risk for microvascular complications (OR 1.32(1.00 – 1.73), OR 1.06(1.00 – 1.12), OR 1.14(1.01 – 1.20), 0R 0.3(0.10 – 0.91) respectively; for macrovascular complications: BMI OR 1.38(1.04 – 1.84) and fat mass OR 1.26(1.00 – 1.58)]. Sexual hormone levels did not influence on glucose control or the development of diabetes-related complications. Conclusion Anthrpometric parameters, especially adipose tissue, were associated with glucose control and variability determined by flash glucose monitoring. Furthermore, changes in fat and lean mass were associated with the presence of microvascular and macrovascular complications. Thus, a comprehensive nutritional evaluation might be useful for the evaluation of males with autoimmune diabetes, in order to identify patients with increased risk of complications.